CD8+ T Cell Hyperfunction and Immunometabolism in Murine Models of Chronic Liver Disease - Jorritsma, Katrina (Université d'Ottawa | University of Ottawa, 2024)
Chronic liver disease, whether viral or metabolic, has negative impacts on local and systemic immune function. Notably, CD8+ T cells, which are vital in the immune response to intracellular pathogens and neoplasms, are impacted in their metabolic programming and function. We aimed to further characterize immune impairments in murine models replicating HCV infection and MASLD pathology. We hypothesized that in advanced liver fibrosis, altered CD8+ T cell mitochondrial fitness and upregulated glycolysis are associated with hyperfunction, potentially driving elevated effector functions. In diet-induced liver disease, generalized CD8+ T cell hyperfunction was observed, characterized by elevated GrzB and IFN-𝛾 expression. This was accompanied by transient elevations in ROS and mitochondrial potential as well as upregulated glycolysis and mitochondrial respiration, in a sex-dependent manner. In conclusion, we report that circulating CD8+ T cells are hyperfunctional in a murine model of diet-induced liver disease, replicating many features of MASH.
Keywords: liver fibrosis; CD8+ T cell; MASLD; HCV; immunometabolism; steatosis